2016
DOI: 10.1021/acs.jpclett.6b00995
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange Combined with Kirkendall Effect in the Preparation of SnTe/CdTe and CdTe/SnTe Core/Shell Nanocrystals

Abstract: Controlling the synthesis of narrow band gap semiconductor nanocrystals (NCs) with a high-quality surface is of prime importance for scientific and technological interests. This Letter presents facile solution-phase syntheses of SnTe NCs and their corresponding core/shell heterostructures. Here, we synthesized monodisperse and highly crystalline SnTe NCs by employing an inexpensive, nontoxic precursor, SnCl2, the reactivity of which was enhanced by adding a reducing agent, 1,2-hexadecanediol. Moreover, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 91 publications
9
54
2
Order By: Relevance
“… 10 12 The knowledge accumulated so far on CE reactions has enabled, this last year alone, the synthesis of new types of NHs, such as CdS nanowires covered by a monolayer of MoS 2 , 13 Cu 2 S-decorated CdS nanorods (NRs), 14 and new core@shell NC systems such as Mn 3 O 4 @CoMn 2 O 4 –Co x O y , 15 Ag–Zn–In-S@ZnS, 16 and SnTe@CdTe. 17 20 Moreover, the number of new NC materials that can be accessed by CE with control over the shape, 21 25 crystal structure, 26 and composition 27 34 has also increased significantly. In turn, these advanced nanostructures have found application in many different fields such as bioimaging, 16 , 20 , 28 , 30 , 35 chemical sensing, 30 supercapacitors, 21 electro- or photocatalysis, 14 , 15 and spintronic or optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“… 10 12 The knowledge accumulated so far on CE reactions has enabled, this last year alone, the synthesis of new types of NHs, such as CdS nanowires covered by a monolayer of MoS 2 , 13 Cu 2 S-decorated CdS nanorods (NRs), 14 and new core@shell NC systems such as Mn 3 O 4 @CoMn 2 O 4 –Co x O y , 15 Ag–Zn–In-S@ZnS, 16 and SnTe@CdTe. 17 20 Moreover, the number of new NC materials that can be accessed by CE with control over the shape, 21 25 crystal structure, 26 and composition 27 34 has also increased significantly. In turn, these advanced nanostructures have found application in many different fields such as bioimaging, 16 , 20 , 28 , 30 , 35 chemical sensing, 30 supercapacitors, 21 electro- or photocatalysis, 14 , 15 and spintronic or optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…For the samples that were subsequently used in devices the initial ATR results are shown in Figure 6.2. These spectra are similar to those previously reported in the literature for these materials [223,[226][227][228][229]. The largest SnTe QDs at 13.6 nm did not make reliable devices but are included to show the band edge progression with size.…”
Section: Xrd and Absorbancesupporting
confidence: 86%
“…It has been suggested that this feature is an LSPR [228], but if that were so it must change energy as the QD size and composition varies [231]. As well as noting the large variation in size and composition of the QDs shown here, these MIR absorption features have also been reported in various forms of SnTe QDs that are reported as being both Sn deficient [227] and Sn rich [228]. This strongly implies that the feature is a result of Sn-related surface chemistry rather than an LSPR or intraband state.…”
Section: Absorbance Featuressupporting
confidence: 60%
See 2 more Smart Citations